Characterization and Functional Test of Canine Probiotics - Jang, Hyun-Jun; Son, Seungwoo; Kim, Jung-Ae; Jung, Min Young; Choi, Yeon-jae; Kim, Dae-Hyuk; Lee, Hak Kyo; Shin, Donghyun; Kim, Yangseon (Frontiers in Microbiology, 2021)
Probiotics can modulate the composition of gut microbiota and benefit the host animal health in multiple ways. Lactic acid bacteria (LAB), mainly Lactobacillus and Bifidobacterium species, are well-known microbes with probiotic potential. In the present study, 88 microbial strains were isolated from canine feces and annotated. Among these, the four strains CACC517, 537, 558, and 566 were tested for probiotic characteristics, and their beneficial effects on hosts were evaluated both in vitro and in vivo; these strains exhibited antibiosis, antibiotic activity, acid and bile tolerance, and relative cell adhesion to the HT-29 monolayer cell line. Byproducts of these strains increased the viability and decreased oxidative stress in mouse and dog cell lines (RAW264.7 and DH82, respectively). Subsequently, when the probiotics were applied to the clinical trial, changes in microbial composition and relative abundance of bacterial strains were clearly observed in the experimental animals. Experimental groups before and after the application were obviously separated from PCA analysis of clinical results. Conclusively, these results could provide comprehensive understanding of the effects of probiotic strains (CACC517, 537, 558, and 566) and their industrial applications.